Design of wearable social distancing card for enhancing public health safety compliance - Soe, Min Thu; Yang, Darren Chua Lik; Swee, Sim Kok; Kit, Wong Wai (Edelweiss Applied Science and Technology, 2025)
During the COVID-19 pandemic, physical distancing has been essential in preventing the virus’s spread. The WHO has implemented physical distancing with at least one meter between individuals. Despite widespread awareness, people often forget to maintain a safe distance in public spaces. This paper addresses this issue by proposing an innovative solution: a wearable social distance card. The objective of this paper is to design a wearable device equipped with modern sensor technology to detect and promote safe distance practices. This device integrates ultrasonics and passive infrared sensors, an Arduino UNO, a buzzer, and an LCD display. The device uses high-frequency sound waves from ultrasonic sensors to measure the distance between individuals in real-time. When individuals reach the predetermined safe distance threshold, the buzzer emits a sound to notify both people to maintain a proper distance. A microcontroller-based wearable social distancing card helps the community practice social distancing. The prototype demonstrates accuracy in distance measurements, exhibiting an average deviation of ±4 cm. This wearable card aids in encouraging social distancing practices, supporting public health efforts to mitigate the spread of infectious diseases. The design represents a significant step forward in promoting social distancing compliance.